INTELEGENSI GANDA SEBAGAI BASIS PEMBELAJARAN - Alfauzan Amin (Institut Agama Islam Negeri Bengkulu, 2011)
This article aim to to know how study strategy base on Multipel Intelegensi. Strategy Study base on Multiple Intelligences (MI) represent a number of engineered step pursuant to tendency of intellegence of student to reach the target of study. In Islam, construction of edukatif interaction do not only limited to humanizing human being only pursuant to human being eksistensi under the sun eye (ardh fil khalifah), but also humanize human being as Allah slave. Exploiting Strategy study base on MI can be used in Islamic education interaction as effort physic balance tuition, liver and mind, grow pre-eminent person with akhlaqul karimah, and also guide human being comprehend and Islam teaching applicati hollisticly